2012
DOI: 10.1523/jneurosci.4908-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Listening Conditions and Memory Load Drive a Common Alpha Oscillatory Network

Abstract: How does acoustic degradation affect the neural mechanisms of working memory? Enhanced alpha oscillations (8 -13 Hz) during retention of items in working memory are often interpreted to reflect increased demands on storage and inhibition. We hypothesized that auditory signal degradation poses an additional challenge to human listeners partly because it draws on the same neural mechanisms. In an adapted Sternberg paradigm, auditory memory load and acoustic degradation were parametrically varied and the magnetoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
196
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(230 citation statements)
references
References 60 publications
24
196
7
3
Order By: Relevance
“…Recent research has shown that acoustic degradation (vocoding) of the signal increases alpha oscillations during listening, suggesting that enhanced alpha power is not only modulated by changing domain-general requirements such as the number of stored items, but that challenges arising from mild-to-severe sensory degradation also affect this system. Both manipulations cause an enhancement of oscillatory power in the same time-frequency range (Obleser et al 2012). Notably, a recent study on alpha power modulation using a working memory paradigm in older hearing-impaired listeners showed that the degree of hearing loss predicted alpha power enhancement (Petersen et al 2015).…”
Section: Physiological Measuresmentioning
confidence: 98%
“…Recent research has shown that acoustic degradation (vocoding) of the signal increases alpha oscillations during listening, suggesting that enhanced alpha power is not only modulated by changing domain-general requirements such as the number of stored items, but that challenges arising from mild-to-severe sensory degradation also affect this system. Both manipulations cause an enhancement of oscillatory power in the same time-frequency range (Obleser et al 2012). Notably, a recent study on alpha power modulation using a working memory paradigm in older hearing-impaired listeners showed that the degree of hearing loss predicted alpha power enhancement (Petersen et al 2015).…”
Section: Physiological Measuresmentioning
confidence: 98%
“…Error bars indicate the SE for intrasubject comparisons. (Spitzer, Fleck, & Blankenburg, 2014;Obleser, Wöstmann, Hellbernd, Wilsch, & Maess, 2012b), difficulty of lexical integration (Strauss, Kotz, Scharinger, & Obleser, 2014), and processing effort in case of degraded speech (Obleser et al, 2012b;Obleser & Weisz, 2012). Since some studies found alpha activity to correlate with task difficulty while others reported the opposite constellation, alpha power and task demands seem to be related in a rather complex manner.…”
Section: Alpha Powermentioning
confidence: 98%
“…XXXX; Kuchinsky et al 2013;Piquado et al 2010;Zekveld & Kramer 2014;Zekveld et al 2010), heart rate, skin conductance, skin temperature, EMG activity (e.g., Mackersie & Cones 2011), heart rate variability (e.g., Mackersie & Calderon-Moultrie, this issue, pp. XXXX), fMRI activity (Wild et al 2012), ERPs (Obleser & Kotz 2011), and EEG alpha power (Obleser et al 2012) (see McGarrigle et al 2014, for a summary of listening effort studies using physiological measures published between 2008 and 2013). A common element of these psychophysiological studies on listening effort is that they examined the effects of variables related to listening difficulty on the physiological measures of interest.…”
Section: Introductionmentioning
confidence: 99%